METHODS OF GROWING MEDICINAL PLANTS IN INVITRO CONDITIONS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Methods for growing medicinal plants in vitro make it possible to reproduce biological processes in laboratory conditions and control the physiological state of plants. These methods play an important role in changing the genetics of plants, quickly obtaining quality crops and protect ix from harmful diseases. Using in vitro technologies, it is possible to accelerate the propagation of medicinal plants, improve various external characteristics and growth rate.